Progress towards the two-thirds conjecture on locating-total dominating sets - Chakraborty, Dipayan; Foucaud, Florent; Hakanen, Anni; Henning, Michael A.; Wagler, Annegret K. (Elsevier, 2025)
We study upper bounds on the size of optimum locating-total dominating sets in graphs. A set S of vertices of a graph G is a locating-total dominating set if every vertex of G has a neighbor in S, and if any two vertices outside S have distinct neighborhoods within S. The smallest size of such a set is denoted by γtL(G). It has been conjectured that γtL(G)≤2n3 holds for every twin-free graph G of order n without isolated vertices. We prove that the conjecture holds for cobipartite graphs, split graphs, block graphs and subcubic graphs.